Pancasila and the Recontextualization of Indonesia’s State Identity: International Relations Approach - Lukito, Wendrik Sandwi; Permana, Aditya; Prasetyo, Ardian (Badan Pembinaan Ideologi Pancasila, 2022)
Indonesia is a state with its uniquely own Pancasila as a national ideology. More than just an ideology, Pancasila has been proved multiple times acts as a unifying factor for Indonesia. Furthermore, many scholars and political leaders of Indonesia defined that the state identity of Indonesia is deeply embedded within Pancasila. Pancasila is the unifying factor for Indonesia, which means that multiculturalism, various religions, ethnic groups, and races, could exist and all be tied up within Pancasila, which is already well-known in the domestic sector. But the question that arose is, how do other states view Indonesia? Does the Pancasila identity featured by Indonesia also seen by other states in the international sector? To answer this question, one must clarify with the International Relations approach as a relevant discipline. Through this paper, the results found out that there have been many attempts to show that the state identity of Indonesia is embedded with Pancasila in the international sector.